(untitled) (Indonesian Sports Justice Review, 2024)
Diversity and inclusion are critical factors in ensuring fair representation and access to opportunities within Indonesia’s sports sector. This paper explores the legal framework that governs the inclusion of minority athletes—whether based on ethnicity, religion, or disability—within Indonesia’s sports landscape. By reviewing national sports policies, legal protections for minority groups, and case studies from various sports federations, this study evaluates how effectively the legal system supports minority athletes. The research further examines the challenges faced by these athletes, from cultural biases to inadequate infrastructure, and suggests legislative reforms to create an inclusive sports environment. Through qualitative interviews with minority athletes and sports administrators, the paper outlines strategies to enhance diversity and inclusion in Indonesian sports, focusing on legal provisions, institutional support, and grassroots initiatives.